Supplementary High-Input Impedance Voltage-Mode Universal Biquadratic Filter Using DVCCs. (6th September 2012) - Mohan, Jitendra; Maheshwari, Sudhanshu
Abstract : To further extend the existing knowledge on voltage-mode universal biquadratic filter, in this paper, a new biquadratic filter circuit with single input and multiple outputs is proposed, employing three differential voltage current conveyors (DVCCs), three resistors, and two grounded capacitors. The proposed circuit realizes all the standard filter functions, that is, high-pass, band-pass, low-pass, notch, and all-pass filters simultaneously. The circuit enjoys the feature of high-input impedance, orthogonal control of resonance angular frequency (ω o ), and quality factor ( Q ) via grounded resistor and the use of grounded capacitors which is ideal for IC implementation.